2006
DOI: 10.4315/0362-028x-69.4.878
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Mycobacterium avium subsp. paratuberculosis in the Presence of Hexadecylpyridinium Chloride, Natamycin, and Vancomycin

Abstract: A design-of-experiments approach was used to examine the effect of hexadecylpyridinium chloride (HPC), alone or in combination with the antibiotics vancomycin and natamycin, on the growth of Mycobacterium avium subsp. paratuberculosis (MAP). At concentrations above 74.4 microg/ml, HPC had a highly significant detrimental effect on the growth of MAP, whereas natamycin at 10.8 and 21.6 microg/ml and vancomycin at 5.2 and 10.4 microg/ml did not have such an effect. Titration of the amount of HPC tolerated by MAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…One explanation for this may be that many of the cultures observed in this study had fewer than 10 cfu/g. Although, HEYA culture is the long-standing method, often used as a gold standard for comparison, it has been observed that the decontamination procedure is detrimental to MAP growth (Johansen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this may be that many of the cultures observed in this study had fewer than 10 cfu/g. Although, HEYA culture is the long-standing method, often used as a gold standard for comparison, it has been observed that the decontamination procedure is detrimental to MAP growth (Johansen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These authors attribute this phenomenon to a decrease of viable MAP bacteria due to the decontamination protocol for fecal samples. This especially concerns the reduction of cultivated bacteria in fecal samples from cows shedding the pathogen in low numbers (Reddacliff et al, 2003;Johansen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The pellet was then weighed, using the conversion where 1 mg is equivalent to 1 × 10 7 CFU. CFU counts were then confirmed via serial dilution on 7H11 plates, where 7H11 plates were supplemented with 2 mg/L mycobactin J (Allied Monitor), 10% OADC, 10µg/mL vancomycin (V2002, Sigma) 20µg/mL amphotericin B(A2942-20ML, Sigma-Aldrich), and 30µg/mL nalidixic acid (N8878, Sigma) to prevent culture contamination [74,75]. GFP-MAP cultures used in all experiments were plated on blood agar plates to ensure the absence of other bacteria.…”
Section: Map Culturementioning
confidence: 99%